Growth, Health, and Carcass Traits of Broilers Supplemented with Acalypha australis L. Leaf Extract, Whey Protein, or their Combination in the Diet - S. Sugiharto; I. Agusetyaningsih; E. Widiastuti; H. I. Wahyuni; T. Yudiarti; T. A. Sartono (Tropical Animal Science Journal, 2023)
The study aimed to investigate the effect of dietary administration of Acalypha australis L. leaf extract, whey powder, or a combination of both on the growth, physiological condition, and carcass traits of broilers. A total of 392 broiler chicks was divided into four groups based on a fully randomized design, including (1) control (C, basal feed without additives), (2) basal feed supplemented with 1% Acalypha australis L. leaf extract (AALE), (3) basal feed with 1% whey powder (WHEY), and (4) basal feed with 1% Acalypha australis L. extract and 1% whey powder (AALEWHEY). Samples (i.e., internal organs, blood, intestinal digesta, small intestinal segments, and breast and thigh meats) were collected on day 33. Data were treated with an analysis of variance followed by Duncan’s multiple analysis. Treatments did not affect body weight, feed intake, and feed conversion ratio (p>0.05). Abdominal fat was higher in the treated broilers than in the control (C) (p<0.05). The serum high-density lipoproteins (HDL) were lower in AALE, WHEY, and AALEWHEY groups than in the control (C) (p<0.05). Serum creatinine concentrations were higher in WHEY and AALEWHEY groups than in C and AALE groups (p<0.05). The AALE, WHEY, and AALEWHEY groups had higher duodenal villi height than C group (p<0.05). The villi height to crypt depth ratios were higher in the jejunum of the WHEY and AALEWHEY group than in the C group (p<0.05). The pH of breast meat was higher in the C group than in AALE and AALEWHEY groups (p<0.05). The lightness values of breast meats were lower in the AALEWHEY group than in the other groups (p<0.05). The redness values of breast meats were lower in the C group than in the AALE, WHEY, and AALEWHEY groups, while the yellowness values were lower in C and AALE groups than in WHEY and AALEWHEY groups (p<0.05). The pH values of thigh meats were higher in the AALE group than in control (C), WHEY, and AALEWHEY groups (p<0.05). In conclusion, the treatment of broilers with leaf extract of Acalypha australis L., whey powder, or a combination of both improved intestinal morphology and meat quality without affecting the growth performance of broilers.